Perilaku Caring Perawat dan Kepuasan Pasien di Ruang Perawatan - Jusamaliah; Siokal, Brajakson; Amir, Haeril; Tutik Agustini (Window of Nursing Journal, 2024)
Health services by hospitals in Indonesia in the digitalization era are becoming a competition between government and private hospitals. One indicator of the quality of nursing services is patient satisfaction. The caring attitude given will get a sense of satisfaction from the patient. This study aims to determine the relationship between caring behavior and patient satisfaction in the Baji Nyawa treatment room at Labuang Baji Hospital. The design of this study was cross sectional, the sampling technique used was total sampling technique. The sample in this study amounted to 65 respondents. The statistical test carried out was Fisher Exact. The results showed that there was a relationship between nurse caring behavior and patient satisfaction with a p-value of 0.000 (<0.05) with a good criterion caring behavior value of 60 patients (92.3%) and patients who were satisfied as many as 59 patients (90.8%). The conclusion of this study is that the caring behavior of nurses has a relationship with patient satisfaction, so the better the caring given by the nurse, the level of patient satisfaction will increase. Therefore, it is expected to maintain and improve the caring behavior of nurses so that patients feel satisfied and continue to choose to use the services at Labuang Baji Hospital.